Space weather impacts on aviation: bridging scientific understanding and operational implications - Wang, Y.; Luo, R. D.; Wei, F. S.; Feng, X. S.; Wang, B. Y.; Zuo, P. B.; Jiang, C. W.; Xu, X. J.; Zhou, Z. L. (Frontiers in Astronomy and Space Sciences, 2025)
Space weather, long considered a peripheral concern for aviation, is increasingly recognized as a significant systemic factor influencing global flight operations. While its impact on communication, navigation, and power systems is well-documented, the broader contribution of space weather to flight delays and cancellations has been historically underestimated, with attention largely confined to polar route disruptions. This perspective calls for a paradigm shift, highlighting the systemic effects of space weather on flight delays and cancellations worldwide and stressing the urgent need to integrate space weather considerations into aviation research, operational frameworks, and strategic planning. Building on recent analyses of U.S. airline data (2024) and prior investigations of Chinese hub airports (2015–2019), we reveal how understanding these impacts can transform aviation operations, improving efficiency and resilience in an interconnected global network. By moving beyond a traditionally siloed approach, this perspective uncovers a previously underappreciated global challenge with profound implications for the future of air travel. We advocate for interdisciplinary collaboration, advanced real-time monitoring, and predictive analytics to enhance aviation resilience and operational efficiency amidst escalating space weather activity.